2017
DOI: 10.1101/cshperspect.a029330
|View full text |Cite
|
Sign up to set email alerts
|

Loss of E-Cadherin-Dependent Cell–Cell Adhesion and the Development and Progression of Cancer

Abstract: Classical cadherins are the key molecules that control cell-cell adhesion. Notwithstanding this function, it is also clear that classical cadherins are more than just the "glue" that keeps the cells together. Cadherins are essential regulators of tissue homeostasis that govern multiple facets of cellular function and development, by transducing adhesive signals to a complex network of signaling effectors and transcriptional programs. In cancer, cadherins are often inactivated or functionally inhibited, resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
123
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(126 citation statements)
references
References 169 publications
(178 reference statements)
2
123
0
1
Order By: Relevance
“…41 Loss of cell-cell adhesion associated with CDH1 abnormalities contributes to both the development and progression of cancers. 42 FOXA2 is a positive regulator of CDH1 expression and altered FOXA2 activity has been linked to epithelial-to-mesenchymal transition (EMT) in breast and pancreatic cancer. 33, 34 It is important to note, however, that it remains uncertain if loss of CDH1 drives EMT or if dysregulation of CDH1 is a result of EMT.…”
Section: Discussionmentioning
confidence: 99%
“…41 Loss of cell-cell adhesion associated with CDH1 abnormalities contributes to both the development and progression of cancers. 42 FOXA2 is a positive regulator of CDH1 expression and altered FOXA2 activity has been linked to epithelial-to-mesenchymal transition (EMT) in breast and pancreatic cancer. 33, 34 It is important to note, however, that it remains uncertain if loss of CDH1 drives EMT or if dysregulation of CDH1 is a result of EMT.…”
Section: Discussionmentioning
confidence: 99%
“…In tumors, it functions as a powerful molecular barrier that inhibits cancer cell proliferation, shedding, invasion, and metastasis . The absence of functional E‐cadherin possibly caused by truncating mutations, loss of heterozygosity, and transcriptional repression is causal for invasive lobular breast carcinoma, which is a subtype of breast cancer . In addition, it has shown that E‐cadherin improves IGF1R recruitment to adherens junctions, possibly resulting in receptor sequestration and signaling repression.…”
Section: Discussionmentioning
confidence: 99%
“…21 The absence of functional E-cadherin possibly caused by truncating mutations, loss of heterozygosity, and transcriptional repression is causal for invasive lobular breast carcinoma, which is a subtype of breast cancer. 22 In addition, it has…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, prior studies that used E-cadherin-coated surfaces have not reported on the formation of E-cadherin adhesions corresponding to this crucial range of elasticity. E-cadherin is a well-known tumor suppressor but is continued to be expressed in many types of cancers [19]. It has been shown that modulation of E-cadherin adhesion may play a key role in cancer progression [20].…”
Section: Introductionmentioning
confidence: 99%